Age-Based Positivity Effects in Imagining and Recalling Future Positive and Negative Autobiographical Events - García-Bajos, Elvira; Migueles, Malen; Aizpurua, Alaitz (Frontiers in Psychology, 2017)
Thoughts about the future reflect personal goals, and projections into the future enrich our emotional life. Researchers have taken an interest in determining whether the tendency to remember more positive than negative emotional events observed when recalling past events also appears when remembering imagined future events. The objective of this study was to examine the age-based positivity effect of recall for future positive and negative autobiographical events in young and older adults. Representative future events were first established to develop the cues used to prompt personal future events. In the production task, the participants were presented with eight positive and eight negative random future events of young or older adults as a model and the corresponding cues to generate their own positive and negative future autobiographical events. In the recall task, the participants recovered as many experiences as they could of the model and the positive and negative events produced by themselves. The participants correctly recalled more positive than negative events and committed more errors for negative than positive events, showing a clear tendency in both young and older adults to recall future imagined events as positive. Regarding age, the young adults recalled more events than the older participants whilst the older participants in particular showed better recall of their own imagined future events than the model’s events, and committed more errors when recalling the model’s events than their own imagined events. Regarding the positivity effect in incorrect recall, more than half of the errors were valence changes, most of these being from negative to positive events, and these valence changes were more pronounced in the older than in the younger adults. In general, there were fewer differences between young and older adults in the recall of positive events in comparison with negative events. Our findings suggest that people are well disposed toward recalling positive imagined future events and preserve a positive emotional state, suppressing negative memories.